BTQ Sebagai Ekstrakurikuler Pengembangan Karakter Anak di Sekolah Dasar - Nurkhalisa, Melia; Nur Anggraeni , Putri; Aulia , Tita (Jurnal Multidisiplin Indonesia, 2023)
Character education is an important pillar in national education. Elementary school is the most basic level of formal education, so character education in elementary school is very important. BTQ is an extracurricular activity that can be used to develop children's character in elementary school. BTQ contains noble values ​​that can be instilled in students, such as honesty, responsibility, discipline and courtesy. This research shows that BTQ has great potential to develop children's character in elementary schools. BTQ can help students to develop these noble values ​​through understanding and applying these values ​​in everyday life. This research uses a literature study research method by collecting secondary data and critical analysis of relevant library sources. Then the results of the analysis are presented descriptively to provide an overview of the development of character education through extracurricular activities.